Kondisi Perlindungan Konsumen Di Negara Indonesia Pada Tahun 2019 - M. Makhfudz (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2020)
AbstractThe implementation of consumer protection is far from being resolved. There are still many cases that are detrimental to the buyer. Whereas, in the principle of sales it says